Identification of fasciclin-like arabinogalactan proteins in textile hemp (Cannabis sativa L.): in silico analyses and gene expression patterns in different tissues - Guerriero, Gea (BMC Genomics, 2017)
BACKGROUND: The fasciclin-like arabinogalactan proteins (FLAs) belong to the arabinogalactan protein (AGP) superfamily and are known to play different physiological roles in plants. This class of proteins was shown to participate in plant growth, development, defense against abiotic stresses and, notably, cell wall biosynthesis. Although some studies are available on the characterization of FLA genes from different species, both woody and herbaceous, no detailed information is available on the FLA family of textile hemp (Cannabis sativa L.), an economically important fibre crop. RESULTS: By searching the Cannabis genome and EST databases, 23 CsaFLAs have been here identified which are divided into four phylogenetic groups. A real-time qPCR analysis performed on stem tissues (isolated bast fibres and shivs sampled at three heights), hypocotyls (6-9-12-15-17-20 days-old), whole seedlings, roots, leaves and female/male flowers of the monoecious fibre variety Santhica 27, indicates that the identified FLA genes are differentially expressed. Interestingly, some hemp FLAs are expressed during early phases of fibre growth (elongation), while others are more expressed in the middle and base of the stem and thus potentially involved in secondary cell wall formation (fibre thickening). The bioinformatic analysis of the promoter regions shows that the FLAs upregulated in the younger regions of the stem share a conserved motif related to flowering control and regulation of photoperiod perception. The promoters of the FLA genes expressed at higher levels in the older stem regions, instead, share a motif putatively recognized by MYB3, a transcriptional repressor belonging to the MYB family subgroup S4. CONCLUSIONS: These results point to the existence of a transcriptional network fine-tuning the expression of FLA genes in the older and younger regions of the stem, as well as in the bast fibres/shivs of textile hemp. In summary, our study paves the way for future analyses on the biological functions of FLAs in an industrially relevant fibre crop. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12864-017-3970-5) contains supplementary material, which is available to authorized users.